China’s long march toward rule of law - Peerenboom, R. P. (Cambridge University Press, 2002)
China has enjoyed considerable economic growth recently, in spite of a problematic legal system. Randall Peerenboom asserts that China is in transition from rule by law to a version of rule of law, although not a "liberal democratic" version. In addition to scholars and students, this book is of interest to business professionals, policy advisors, and governmental and non-governmental agencies